On the legal regulation of beekeeping in Belarus - Саскевич, Вероника Васильевна (Journal of the Belarusian State University. Law, 2022)
Acts of the Belarusian legislation containing special norms on beekeeping are analysed. The differences in the legal regulation of beekeeping depending on the legal status of the subject of this activity are emphasised. It is concluded that it is advisable to adopt the legislative framework for beekeeping and legal measures to stimulate it. The necessity of implementing a unified approach to the regulation of the placement and arrangement of apiaries, improving the legal regulation of pedigree beekeeping has been substantiated. It is proposed to recognise the beekeeping of individuals, including income generation, as a type of non-commercial activity of citizens and to provide special legal grounds for the land plots use for beekeeping.
Keywords: legal regulation of beekeeping; agrarian law; agriculture; veterinary and sanitary regulations; pedigree beekeeping; land rights